Aeromedical evacuation during the health crisis caused by SARS-CoV-2 in the state of Amazonas – Brazil (Research, Society and Development, 2022)
Objective: To describe the experience of military nursing in preparing the embarkation of critically ill patients from Amazonas to other states in Brazil during the health crisis caused by the pandemic of COVID-19. Method: Case report built with the observation of the flight nurse about the importance of boarding preparation for the safety of aeromedical transport. Discussion: Still on the ground, the team is concerned with the configuration of the aircraft, with the configuration of beds (which will happen in a personalized way), in addition to the systematic testing of aeromedical equipment and replacement of supplies and medicines until landing safely. Conclusion: Embarkation planning is an indispensable step for the safe transportation of critically ill patients. The study brings an approach to the specific care in the pre-flight of aeromedical evacuation. In this sense, the nurse develops the actions of boarding planning, based on the experience of assistance to critical patients and, participates in the multidisciplinary team during the flight.